Relationship Between Economic Status, Infectious Diseases and Urinary Iodine Excretion with Stunting Incidence of Elementary School Children in IDD Endemic Areas, Enrekang Regency - Abri, Nur; Thaha, Abdul Razak; Jafar, Nurhaedar (Journal of Health and Nutrition Research, 2022)
This study aimed to determine the relationship of economic status, infectious diseases, and Urinary Iodine Excretion (UIE) with the incidence of stunting in elementary school children in IDD endemic areas, Enrekang Regency. This research was an observational analytic study with a cross-sectional approach. Subjects in this study were taken by purposive sampling as many as 100 children aged 6-12 years. Research data were collected using a questionnaire, microtoise, and UIE Lab Test and then processed using the chi-square test. The results showed that the proportion of stunting was 72.2% and normal was 28.0%, the low family economy was 82.0%, infectious disease was 79.0%, and low urinary iodine deficiency was 21.0%. The chi-square test showed that there was a significant relationship between economic status (p=0.045) and infectious diseases (p=0.012) with the incidence of stunting, but there was no relationship between UIE and stunting (p=1,000). The economic status of parents and a history of infectious diseases contribute to the incidence of stunting. Modification of parents' crops by harvesting crops in a short time is recommended to increase family income and increasing children's healthy and clean behaviour is considered necessary to prevent infectious diseases.